1996
DOI: 10.1002/(sici)1097-0290(19961220)52:6<672::aid-bit5>3.3.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of mycelial morphology on impeller type and agitation intensity

Abstract: The influence of the agitation conditions on the morphology of fenicillium chrysogenum (freely dispersed and aggregated forms) was examined using radial (Rushton turbines and paddles), axial (pitched blades, propeller, and Prochem Maxflow T), and counterflow impellers (Intermig). Culture broth was taken from a continuous fermentation at steady state and was agitated for 30 min in an ungassed vessel of 1.4-L working volume. The power inputs per unit volume of liquid in the tank, fNL, ranged from 0.6 to 6 kW/m3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
1
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 104 publications
(108 citation statements)
references
References 0 publications
5
101
1
1
Order By: Relevance
“…1, Table II) has been found to correlate better with morphological and fragmentation data than power (P) per unit volume (V L ) (Justen et al, 1996(Justen et al, , 1998bAmanullah et al, 1999), impeller power is reported in terms of EDCF. For each sample time, EDCF was determined for each of the three impellers in the particular tank.…”
Section: Calculation Of Edcf and Aeration Number (N Ae )mentioning
confidence: 95%
See 1 more Smart Citation
“…1, Table II) has been found to correlate better with morphological and fragmentation data than power (P) per unit volume (V L ) (Justen et al, 1996(Justen et al, , 1998bAmanullah et al, 1999), impeller power is reported in terms of EDCF. For each sample time, EDCF was determined for each of the three impellers in the particular tank.…”
Section: Calculation Of Edcf and Aeration Number (N Ae )mentioning
confidence: 95%
“…In stirred bioreactors, impeller shear stress often prevents cells from forming pellets and visual inspection in many processes shows dispersed growth being much more prevalent (Tucker et al, 1992;Olsvik and Kristiansen, 1994). Studies have shown that in these cases the vast majority of biomass resides in clumps (Tucker et al, 1992;Justen et al, 1996;Amanullah et al, 1999). However, most of these observations have come from laboratory or pilot-scale fermentations.…”
Section: Introductionmentioning
confidence: 99%
“…Pellets are spherical or ellipsoidal masses of hyphae with variable internal structure, ranging from loosely packed hyphae, forming ''fluffy'' pellets, to tightly packed, compact, dense pellets (Papagianni, 2004). The dispersed form consists of branched and unbranched hyphae (freely dispersed) and aggregates (clumps) (Justen et al 1996). The exact mechanism behind pellet formation is not known, and the mechanism probably varies from species to species, perhaps even from strain to strain.…”
Section: *Corresponding Authormentioning
confidence: 99%
“…It should be noted that Justen et al (1996) used projected area to describe of the dispersed forms in their agitation trials. Clearly, one method for all forms would be valuable.…”
Section: Pelleted Morphologymentioning
confidence: 99%